2014
DOI: 10.3390/ijerph110504926
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate Exposure and Thyroid Function in Ammonium Perchlorate Workers in Yicheng, China

Abstract: The impact of low level dust on the thyroid function of workers chronically exposed to ammonium perchlorate (AP) is uncertain and controversial. The aim of this study was to examine whether workers in China with long-term (>3 years) occupational exposure to low levels of AP dust had affected thyroid homeostasis. Mean occupational exposures to AP dust ranged from 0.43 to 1.17 mg/m3. Geometric means of post-shift urinary perchlorate levels were 20.5 µg/L for those exposed and 12.8 µg/L for the controls. No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… Although these correlations are clearly demonstrated in experimental studies, the relationship between human perchlorate exposure and thyroid function disfunction are extremely controversial . Actually, even though some reports have shown an inverse correlation between urinary perchlorate concentration and thyroid hormone levels, other studies have not consistently supported this correlation . Even so, there is a general agreement that perchlorate exposure seems to be more harmful to susceptible individuals, as pregnant women, children and individuals living in iodine deficient areas …”
Section: Discussionmentioning
confidence: 97%
“… Although these correlations are clearly demonstrated in experimental studies, the relationship between human perchlorate exposure and thyroid function disfunction are extremely controversial . Actually, even though some reports have shown an inverse correlation between urinary perchlorate concentration and thyroid hormone levels, other studies have not consistently supported this correlation . Even so, there is a general agreement that perchlorate exposure seems to be more harmful to susceptible individuals, as pregnant women, children and individuals living in iodine deficient areas …”
Section: Discussionmentioning
confidence: 97%
“…In particular, perchlorate factory workers and the population of large cities where smog phenomenon occurs are the most vulnerable groups to this type of exposure [6]. Several studies [76][77] conducted on the factory workers, who inhaled dust containing subclinical doses of perchlorate for a few hours a day showed no significant changes in the level of thyroid hormones in the blood compared to the control group, despite the increase in the content of perchlorate excreted in the urine. Study from China also informs about the increased amount of ClO 4…”
Section: Routes Of Exposurementioning
confidence: 99%
“…Apart from the research carried out in the general population, there are some studies concerned on occupational risk of perchlorate exposure in heavy industry employees. Chen et al [129] investigated differences in perchlorate concentration in employees of the fireworks factory in China, who were exposed to perchlorate to varying degrees. The content of ClO 4 − in the urine of employees finishing their shift was median (range) 8.89 (0.92-24.71) μg/L for exposed group (51 people) and 5.56 (0.37-20.55) μg/L control group (41 people).…”
Section: Occupational Risk Assessment In Factory Workersmentioning
confidence: 99%
“…[4] An observational study carried out at an ammonium perchlorate production factory in China found no effect on thyroid function from long-term exposure to ammonium perchlorate. [13].…”
Section: Discussionmentioning
confidence: 99%